2023
DOI: 10.1093/sysbio/syad008
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Rapid Radiation Explains Most Conflicts Among Gene Trees and Well-Supported Phylogenomic Trees of Nostocalean Cyanobacteria

Abstract: Prokaryotic genomes are often considered to be mosaics of genes that do not necessarily share the same evolutionary history due to widespread Horizontal Gene Transfers (HGTs). Consequently, representing evolutionary relationships of prokaryotes as bifurcating trees has long been controversial. However, studies reporting conflicts among gene trees derived from phylogenomic datasets have shown that these conflicts can be the result of artifacts or evolutionary processes other than HGT, such as incomplete lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…Given that these are single tree phylogenies, and that some of the smaller sequence alignments do not have high resolving power, it is still possible that these results can be explained by other phenomena such as incomplete lineage sorting of duplicated genes as a consequence of the rapid diversification process occurring around the initial divergence of micro-and macrocyanobacteria. This has been demonstrated recently for incongruences in gene and species trees within the heterocystous cyanobacteria (Pardo-De la Hoz et al, 2023) and is likely to affect other cyanobacterial relationships as well. Future analyses should also consider the conservation of gene synteny in the cluster across taxa and disparities in G+C content in the FaRLiP cluster relative to the rest of the genome to infer and single out HGT events more confidently.…”
Section: A Timeline For the Evolution Of Farlip Photosystemsmentioning
confidence: 61%
“…Given that these are single tree phylogenies, and that some of the smaller sequence alignments do not have high resolving power, it is still possible that these results can be explained by other phenomena such as incomplete lineage sorting of duplicated genes as a consequence of the rapid diversification process occurring around the initial divergence of micro-and macrocyanobacteria. This has been demonstrated recently for incongruences in gene and species trees within the heterocystous cyanobacteria (Pardo-De la Hoz et al, 2023) and is likely to affect other cyanobacterial relationships as well. Future analyses should also consider the conservation of gene synteny in the cluster across taxa and disparities in G+C content in the FaRLiP cluster relative to the rest of the genome to infer and single out HGT events more confidently.…”
Section: A Timeline For the Evolution Of Farlip Photosystemsmentioning
confidence: 61%
“…For a specific group of species, phylogenetic trees constructed from individual genes often show inconsistency with each other [61,62]. As the number of taxa increases, single-gene phylogenetic trees typically have low statistical support [63]. Studies have reported that when using the same parameters and the same program, approximately 9% to 18% of single-gene phylogenetic trees cannot replicate the same topology [64].…”
Section: Advanced Computational Integrative Methods For Inferring Phy...mentioning
confidence: 99%
“…Of the 24 cyanobiont genomes, 21 belong to Nostoc spp., with the remainder belonging to Rhizonema spp . [ 52 ]. However, the first attempts based on full genome data of free-living and lichenized Nostoc strains identified genes potentially involved in symbioses, which may help to improve taxonomic resolution [ 53 ].…”
Section: The Research Roadmapmentioning
confidence: 99%
“…The increased isolation efforts of INCb will expand the genomic data, and result in the first publicly available unicellular cyanobiont genome. Rapidly growing numbers of genome sequences of cyanobacteria provide an increasing amount of evidence that single genetic markers, several markers, or morphological data have only limited power when recognizing the diversity between and within species [ 52 , 54 ]. Additionally, it is likely that one lichen thallus can host several lineages of cyanobionts due to the potentially huge diversity at the genome level within single lineages of cyanobacteria [e.g.…”
Section: The Research Roadmapmentioning
confidence: 99%